Gael force : a history of football at Queen's, 1882-2016 - Daub, Mervin A. (McGill-Queen's University Press, 2018)
"Football at Queen's University has one of the richest, and certainly one of the longest, histories of any sport in Canada. The Golden Gaels have been a presence in Canadian football at both the amateur and professional level since 1882. Gael Force traces this history, chronicling the team's ups and downs and integrating them within the history of the university, the country, and the sport in general. Gael Force provides a wealth of interesting facts and engaging anecdotes as well as profiles and photographs of the coaches, captains, and players. Merv Daub takes the reader through a century of Queen's football, from the first "Dominion" championship in 1893 with Curtis and his boys, through three consecutive Grey Cup wins in the 1920s, the 1934-35 victory of the "Fearless Fourteen," the 1955 season when Gus Braccia, Ronnie Stewart, Gary Schreider, Lou Bruce, Al Kocman, "Jocko" Thompson, and the rest of that "band of merry men" brought Queen's back into the limelight, the golden years of the 1960s, to the 1978 and 1992 Vanier Cup championship seasons. Gael Force is a tribute to the long-standing football legacy at Queen's and an important historical and sociological study of college sport in Canada. This new edition of Gael Force, originally published in 1996, brings the history of football at Queen's up to date, stretching from its beginnings until the end of 2016. Golden Gaels have been a presence in Canadian football at both the amateur and professional level since 1882 and this history chronicles the team's ups and downs and integrating them within the history of the university, the country, and the sport in general."--